2017
DOI: 10.1103/physrevphyseducres.13.010110
|View full text |Cite
|
Sign up to set email alerts
|

To draw or not to draw? Examining the necessity of problem diagrams using massive open online course experiments

Abstract: Previous research on problem diagrams suggested that including a supportive diagram, one that does not provide necessary problem solving information, may bring little, or even negative, benefit to students' problem solving success. We tested the usefulness of problem diagrams on 12 different physics problems (6A/B experiments) in our massive open online course. By analyzing over 8000 student responses in total, we found that including a problem diagram that contains no significant additional information only s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…The current study demonstrated two such methods using OLM sequences and analysis of student log data. The first is a controlled AB experiment conducted in a single course, similar to the design in two previous studies [5,23]. The second method involves implementing improved instructional design in the same class for consecutive years.…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated two such methods using OLM sequences and analysis of student log data. The first is a controlled AB experiment conducted in a single course, similar to the design in two previous studies [5,23]. The second method involves implementing improved instructional design in the same class for consecutive years.…”
Section: Discussionmentioning
confidence: 99%
“…We employed a flipped online AB experiment design similar to two earlier studies [8,9]. Two versions of online homework were created for two chapters of a calculus-based introductory physics course, covering the topics of mechanical energy and linear momentum.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Question Interaction or a small positive effect of supportive diagrams on problem solving [7]. The reason why the diagram in question Q3 had a positive effect on students' percentages of correct answers could be that it emphasized the initial equal elevations of the bricks (see the Supplemental Material [30]).…”
Section: Diagrammentioning
confidence: 99%
“…More research is needed to determine the role of diagrams in problem solving. A recent large-scale study on usefulness of supportive diagrams has shown their small positive effect on students' scores [7].…”
mentioning
confidence: 99%